A Central Potential with a Massive Scalar Field in a Lorentz Symmetry Violation Environment. (4th June 2019) - Vitória, R. L. L.; Belich, H.
Abstract : We investigate the behaviour of a massive scalar field under the influence of a Coulomb-type and central linear central potentials inserted in the Klein-Gordon equation by modifying the mass term in the spacetime with Lorentz symmetry violation. We consider the presence of a background constant vector field which characterizes the breaking of the Lorentz symmetry and show that analytical solutions to the Klein-Gordon equation can be achieved.